Dinamika Penyebaran Agama Islam di Kerajaan Siantar, 1904-1913 - Dona Ponja; Yusra Dewi Siregar; Anang Anas Azhar (Mahesa Research Center, 2020)
This article discusses the dynamics of the spread of Islam in the Siantar Kingdom at the beginning of the 20th century. The interaction of coastal communities with inland areas through trade routes made this area then influenced by Islam. This study uses the historical method in four writing steps, namely; heuristics, verification or criticism, interpretation, and historiography, with a historical approach. After King Sang Naualuh Damanik embraced Islam, the development of Islam in this area spread quite massively. The king and the preachers and other court officials became the front guard in preaching Islam in Siantar. In the process of spreading, Islam also faced some serious challenges. First, there are still many Siantar people who embrace the religion of their ancestors (Habonaron Do Bona). Second, the entry of Christian missionaries from the RMG (Rheinische Missions Gesellschaft) organization from Germany, which was tasked with evangelizing the people of Simalungun and the coast of Lake Toba. With his increasingly active activities in preaching Islam, finally, Raja Sang Naualuh Damanik was arrested by the Dutch colonialists in 1905. The following year, he was exiled to Bengkasli, Riau. After the exile of the King, the spread of Islam in the Siantar region practically stopped.